Reassessing Hifdz Al-Nasl in the Age of Assisted Reproduction: a Maqashid Al-Shari’ah Perspective on Donor Artificial Insemination - Nasiri Nasiri (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The rapid advancement of Assisted Reproductive Technology (ART), specifically donor artificial insemination, has challenged the traditional boundaries of Islamic family law and bioethics. This research explores the relevance and repositioning of the concept of Hifdz al-Nasl (preservation of lineage) within the framework of Maqashid al-Shari’ah (the higher objectives of Islamic law). Using a qualitative normative-philosophical approach, this study evaluates classical jurisprudence prohibiting third-party genetic intervention against the modern context of genetic certainty and DNA technology. The findings indicate that the traditional